Association analysis of novel polymorphisms in 2′, 5′‐oligoadenylate synthetase gene with reproductive traits in indigenous and cross‐bred cattle of Indian Origin. (25th December 2017) - Alex, R; Ramesha, KP; Singh, U; Kumar, S; Alyethodi, RR; Deb, R; Rai, S; Sharma, S; Sengar, GS; Kumar, A; Prakash, B
Contents: 2′, 5′‐Oligoadenylate synthetases (OAS) are important components of an interferon‐mediated antiviral pathway. No polymorphisms in exonic regions of bovine  OAS1  gene have been identified and associated with reproduction traits. The objective of the study was to detect and evaluate the effects of mutations in exonic region of bovine OAS1 gene with reproduction traits in cattle. DNA samples collected from 250 individual cows of two Indian dairy breeds (Sahiwal and Frieswal) of cattle were used in the study. The genetic variants of the OAS1 gene were identified with polymerase chain reaction–single‐strand conformation polymorphism (PCR‐SSCP) and sequence analysis using seven set of primer pairs. The PCR‐SSCP analysis revealed polymorphism in the fragments comprising of exon 2, exon 5 and first fragment of exon 6 while the fragments of exons 1, 3, 4 and second fragment of exon 6 were monomorphic in Sahiwal and Frieswal cattle. The mutations in the amplified region comprising of exon 2 were found to have significant association with age at first breeding and calving, service period, dry period and pregnancy rate. Significant associations were found between SNPs in the exon 5 and service and dry periods of the animal, whereas the genetic variants in the first fragment of the exon 6 showed significant association with age at first breeding and calving. To our knowledge, this study demonstrated for the first time that the polymorphisms in OAS1 gene were associated with reproductive traits and it can be chosen as a candidate gene for improvement of reproductive performance of cattle.